Investigation of Structures, Vibrational Spectra, and Morphological Characteristics of Undoped and Cobalt-doped Ni-Zn Ferrite - Joko Utomo; Robi Kurniawan; Muhammad Reyza Arief Taqwa; Bakhrul Rizky Kurniawan; Nur Elma Ayu Wahyuni; Adulsman Sukkaew (Universitas Negeri Malang, 2022)
Undoped and Co-doped Nickel Zinc ferrite (NiZnFe2O4) have been successfully prepared using the coprecipitation method with the further annealing treatment at 600 ºC. The structure, image, and vibrational spectra of the materials were investigated respectively by XRD, TEM, and FTIR characterizations. Based on XRD characterization results, both undoped and Co-doped Ni – Zn ferrite possesses a single-phase formation, namely spinel structure without any impurities from other phases. The lattice parameters of Co-doped Ni – Zn ferrite is 8.419 nm which is higher than undoped Ni – Zn ferrite (8.409 nm). Meanwhile, the average particle size obtained based on the results of the TEM characterization is 14.4 nm with slight agglomeration. The results of FTIR characterization on all samples provide information on the presence of metal ion vibrations at frequency bands about 493.78 cm-1 located at the tetrahedral and 514.99 cm-1 occupied at octahedral sites. Those frequency ranges confirmed that both samples have spinel structures.DOI: 10.17977/um024v7i12022p051